Pegylated interferon monotherapy in patients with chronic hepatitis C with low viremia and its relationship to mutations in the NS5A region and the single nucleotide polymorphism of interleukin‐28B. Issue 6 (29th January 2013) - Hayashi, Kazuhiko; Katano, Yoshiaki; Masuda, Hiroko; Ishizu, Youji; Kuzuya, Teiji; Honda, Takashi; Ishigami, Masatoshi; Itoh, Akihiro; Hirooka, Yoshiki; Nakano, Isao; Ishikawa, Tetsuya; Urano, Fumihiro; et al.
<x xml:space="preserve">Abstract</x> Aim Previous studies have suggested that patients with chronic hepatitis C with a low pretreatment hepatitis C virus (HCV) level have a high sustained virological response (SVR) rate, and that there would be a subpopulation of patients in which HCV can be eradicated with pegylated interferon (PEG IFN) alone without a decrease in SVR. However, the efficacy of PEG IFN monotherapy in patients with low HCV RNA levels is unclear. Several studies have reported that interferon sensitivity‐determining region (ISDR) and the single‐nucleotide polymorphism (SNP) of interleukin‐28B (IL‐28B) contribute to IFN response, but these relationships are controversial. The aim of this study was to determine whether the SNP of IL‐28B (rs8099917) and amino acid substitutions in the ISDR among patients with low HCV levels affect the response to PEG IFN monotherapy. Methods One hundred and four patients with low‐level HCV infection were studied. Low HCV level was defined as 100 KIU/mL or less. Results SVR was achieved in 94 patients (92.2%). HCV levels (≤50 KIU/mL) and ISDR (≥2 mutations) were associated with SVR on univariate analysis. The rates of SVR in the patients with IL‐28B genotypes TT, TG and GG were 94.5%, 77.8% and 100%, respectively. The G allele tended to be associated with poor response to IFN therapy (P = 0.0623). On multivariate analysis, the ISDR was the factor predictive of SVR (P = 0.004). Conclusion The ISDR is significantly associated with a good response to PEG IFN monotherapy in patients with low HCV levels.